Doubling of farmers’ income: Push to agri-R&D holds the key - Kumar, Anjani; Bathla, Seema (2018)
The concerns for transforming agricultural sector are getting louder, as the last chance of presenting the full-fledged Union budget of the current political regime is getting closer. Given the formidable challenge of the government to double farmers’ real incomes in the next six years, the farm sector deserves to be the nucleus of the Union budget. During the last three and half years, agriculture has received utmost attention and a good number of measures have been taken to expedite growth and forestall distress faced by farmers in several states. Large investments in irrigation along with key initiatives, such as Pradhan Mantri Krishi Sinchayee Yojana, Soil Health Card Scheme, Pradhan Mantri Fasal Bima Yojana, E-NAM (electronic national agriculture market) and ‘price deficiency payment’ system, to address gaps in minimum support price are expected to yield benefits in due course. However, the push required for strengthening agricultural research & development (Agri-R&D), which is critical for the long-term growth in this sector, remains elusive . The three-year agenda document, brought out by the NITI Aayog, has laid considerable emphasis on accelerating agricultural productivity through the use of high-yield seeds, improved irrigation techniques, precision farming and related technologies. But, the persistence of underinvestment in Agri-R&D remains worrisome.